Environmental Variables for Sustainable Industry Performance with the Green Marketing Mix: Preliminary Study - Bambang Hengky Rainanto, Abdul Talib Bon, Jan Horas V. Purba (International Journal of Advanced Science and Technology, 2020)
This preliminary study is to determine the relationship between the variableEnvironmental Management System (EMS) and Pro-Environmental Behavior in hotelindustry players for Sustainable Industry Performance (SIP) with the 7Ps GreenMarketing Mix (GMM) as mediator. The pilot study was conducted at hotels in the city ofBogor, Indonesia. The background of the research is based on the increasingly frequentoccurrence of environmental impacts due to the impact of tourism development. Hotel isone of the main industries that support tourism needs to create internal andenvironmental conditions in order to be able to do business sustainably. This initialresearch is expected to be a reference conceptual scientific model for research with abroader area or other fields related to the environment and the tourism sector. The resultsof this initial research will be important for other research in the hotel industry and theworld of tourism with the aim of ensuring the sustainability of their business. The sameresearch variable, but different types of objects and research locations, will likely givedifferent results as well.